Does Growing up in Economic Hard Times Increase Compassion? The Case of Attitudes towards Immigration - Maria Cotofan; Robert Dur; Stephan Meier (Tinbergen Institute, 2022)
Recent evidence shows that people who grew up in economic hard times more strongly favor government redistribution and are more compassionate towards the poor. We investigate how inclusive this increase in compassion is by studying how macroeconomic conditions experienced during young adulthood affect immigration attitudes. Using US and global data, we show that experiencing bad macroeconomic circumstances strengthen anti-immigration attitudes for life. Moreover, we find that people become generally more outgroup hostile. Our results thus suggest that the underlying motive for more government redistribution is not a universal increase in compassion, but more self-interested and restricted to one's ingroup.
Keywords: J1; D9; E7; 330; Immigration; Attitudes; Social preferences; Parochialism; Redistribution; Macroeconomic conditions; Impressionable years